The mediation of self-compassion and other constructs: significance in resilience, depression and anxiety among students (Engrami, 2020)
Introduction. Contemporary studies suggest present affective and stress related difficulties such as depressivenes, anxiousness and related states among students of different levels and backgrounds of studies [1,2] hardships that might appear later on, during education and professional activities, depending of the duration and mood severity [3], but also different factors that might play potential protective roles during the whole process [4,5].Objective. To examine the mediation effects of variables positive lateral generalization, perceived social support and self-compassion in a relationship between depression and anxiety with resilience.Method. A cross-sectional research was conducted in Serbian speaking area on 147 students (108 females (73,5%) and 39 males (26,5%)) of different courses and levels of education, and six different hypothethical single mediator models were examined between anxiety, depression and resilience with the intercession of three mediators: perceived social support, lateral generalisation and self-compassion.Results. Results indicate a non-significant relationship between anxiety and perceived social support (r=-0.09; p>0.05) so that assumption for mediation analysis was not met for furter examination for this model. Perceived social support did not mediate the relationship between depression and resilience significantly (b=0.02; p >0.05, 95% Bca CI [-0.03, 0.08]) which was also the case for lateral generalization (b=0.03; p>0.05, 95% Bca CI [-0.01, 0.10]) as well as in the case between anxiety and resilience (b=0.02; p>0.05, 95% Bca CI [-0.01, 0.09]), whilst significant mediation effect of self-compassion was observed both in relationship between depression and resilience (b=-0.24 p
Keywords: lateral generalization; cross-sectional study; social support